2021
DOI: 10.3389/fphar.2021.606245
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Shear-Induced Platelet Aggregation by Xueshuantong via Targeting Piezo1 Channel-Mediated Ca2+ Signaling Pathway

Abstract: XueShuanTong (XST) comprising therapeutically active ginsenosides, a lyophilized extract of Panax notoginseng roots, is extensively used in traditional Chinese medicine to treat ischemic heart and cerebrovascular diseases. Our recent study shows that treatment with XST inhibits shear-induced thrombosis formation but the underlying mechanism remained unclear. This study aimed to investigate the hypothesis that XST inhibited shear-induced platelet aggregation via targeting the mechanosensitive Ca2+-permeable Pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Ginsenoside Rk1 inhibited platelet‐mediated thrombus formation by downregulation of granule release and αβ activation (J. H. Shin, Kwon, Irfan, Rhee, & Lee, 2021). Xueshuantong is composed of ginsenosides to treat ischemic heart and cerebrovascular diseases, and it was found that Xueshuantong suppressed shear‐induced platelet aggregation by targeting piezo1 channel‐mediated Ca 2+ signaling (L. Liu et al, 2021). Meanwhile, another article reported that red GE was embedded in nanomaterials or antithrombotic materials to improve the oral availability of red ginseng and its antithrombotic activity (E. S. Kim, Lee, & Lee, 2021).…”
Section: Recent Findings Of Ginseng In the Treatment Of Vascular Dysf...mentioning
confidence: 99%
“…Ginsenoside Rk1 inhibited platelet‐mediated thrombus formation by downregulation of granule release and αβ activation (J. H. Shin, Kwon, Irfan, Rhee, & Lee, 2021). Xueshuantong is composed of ginsenosides to treat ischemic heart and cerebrovascular diseases, and it was found that Xueshuantong suppressed shear‐induced platelet aggregation by targeting piezo1 channel‐mediated Ca 2+ signaling (L. Liu et al, 2021). Meanwhile, another article reported that red GE was embedded in nanomaterials or antithrombotic materials to improve the oral availability of red ginseng and its antithrombotic activity (E. S. Kim, Lee, & Lee, 2021).…”
Section: Recent Findings Of Ginseng In the Treatment Of Vascular Dysf...mentioning
confidence: 99%
“…When Piezo channels are opened/activated, a cellular signaling cascade is triggered by the Ca 2+ influx through the Piezo channels [ 24 , 50 , 51 , 52 , 53 ]. Zhao et al considered that the extracellular CED has a lot of negative charge, so extracellular cations such as Ca 2+ will be aggregated and will flow through the pore of Piezo channels to cross the cell membrane [ 24 ].…”
Section: The Role Of Piezo Channels In Cellular Mechanotransductionmentioning
confidence: 99%
“…By experimentally stretching epithelial cells in vitro, Gudipaty et al found that mechanical stretch, through the mechanosensitive Piezo1, triggers these cells to pause in early G2 to activate calcium-dependent ERK1/2 phosphorylation and cyclin B transcription, thus prompting these cells to enter mitosis [ 52 ]. Exposure to blood flow shear force in vitro activates the Piezo1 channel, with ensuing Piezo1-mediated Ca 2+ influx in platelets [ 53 ]. An increase in intracellular Ca 2+ level in turn promotes activation of calpain-2 and cleavage of talin1, leading to platelet aggregation [ 53 ].…”
Section: The Role Of Piezo Channels In Cellular Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular scale, increasing evidences suggest that platelets can undergo mechanosensing upon receiving these hemodynamic stimuli. Key players in such mechanosensing processes include von Willebrand factors (VWF) ( Savage et al, 1996 ; Fu et al, 2017 ), fibrinogen ( Butera and Hogg, 2020 ; Peshkova et al, 2020 ), mechanoreceptors including glycoprotein Ib (GPIb) ( Chen et al, 2016 ; Ju et al, 2016 ) and glycoprotein IIb/IIIa (GPIIb/IIIa or integrin α IIb β 3 ) ( Nesbitt et al, 2009 ; Chen Y et al, 2019 ), and mechanosensitive ion channels ( Abbonante et al, 2017 ; Ilkan et al, 2017 ; Liu et al, 2021 ). Further, activated platelets generate contractile forces to stabilize and consolidate the thrombus ( Osdoit and Rosa, 2001 ; Ono et al, 2008 ; Hansen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%